2009
DOI: 10.1093/eurheartj/ehn582
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an echocardiographic multiparametric strategy to increase responders patients after cardiac resynchronization: a multicentre study

Abstract: A multiparametric echocardiographic strategy based on the association of conventional criteria is a better indicator of CRT response than the existing single parametric approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…The number of studies that include more advanced statistical tools is rather limited. Multiple stepwise logistic regression was previously used within the context of our application ( Mädler et al, 2003 ), and multiparametric approaches were proposed to predict response to cardiac resynchronization therapy (CRT) ( Santaularia-Tomas and Abraham, 2009;Lafitte et al, 2009 ). Nonetheless, all these approaches have notable limits for the advanced diagnosis of complex diseases.…”
Section: Multiple Features Analysismentioning
confidence: 99%
“…The number of studies that include more advanced statistical tools is rather limited. Multiple stepwise logistic regression was previously used within the context of our application ( Mädler et al, 2003 ), and multiparametric approaches were proposed to predict response to cardiac resynchronization therapy (CRT) ( Santaularia-Tomas and Abraham, 2009;Lafitte et al, 2009 ). Nonetheless, all these approaches have notable limits for the advanced diagnosis of complex diseases.…”
Section: Multiple Features Analysismentioning
confidence: 99%
“…In the study by Gorcsan et al (30), combination of longitudinal and radial measures by speckle tracking predicted EF response significantly better than either technique alone. Recently, Lafitte et al (31) demonstrated that use of a multiparametric approach that focused on criteria combination Table 1. Carluccio et al Remodeling and Recovery of Function After CRT significantly decreased the rate of false-positive results.…”
Section: Figure 3 Relationship Between Baseline Esvi Intravd and Imentioning
confidence: 99%
“…From another report, it is thought that at least 3 parameters are needed for a reasonable prediction. 54 Suffoletto et al proposed that speckle tracking applied to mid-ventricular short-axis images to calculate the radial strain from multiple circumferential points averaged to 6 segments. 55 The time difference in the peak septal-to-posterior wall strain of ≥130 ms predicted a significant increase in LVEF with a sensitivity of 89% and a specificity of 83%.…”
Section: In Post Prospect Eramentioning
confidence: 99%